2015
DOI: 10.1097/coc.0b013e31829e19be
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Magnetic Resonance Imaging for the Assessment of the Myocardium After Doxorubicin-based Chemotherapy

Abstract: Our data suggests that cMRI has the ability to assess both early structural and functional myocardial changes in association with doxorubicin-based chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…A mild increase in myocardial scaring was also observed. The authors concluded that cMRI and left atrial volume might be early markers of diastolic dysfunction and markers of myocardial fibrosis [40,41].…”
Section: Emerging Cardiac Monitoring Methodologiesmentioning
confidence: 98%
See 1 more Smart Citation
“…A mild increase in myocardial scaring was also observed. The authors concluded that cMRI and left atrial volume might be early markers of diastolic dysfunction and markers of myocardial fibrosis [40,41].…”
Section: Emerging Cardiac Monitoring Methodologiesmentioning
confidence: 98%
“…cMRI is able to assess both the functional and structural components of the myocardium. In a prospective study of 81 childhood cancer patients [40], the primary finding was a significant increase in left atrial volume by cMRI. A mild increase in myocardial scaring was also observed.…”
Section: Emerging Cardiac Monitoring Methodologiesmentioning
confidence: 99%
“…Cardio-oncology: Use of feature tracking for the diagnosis of chemotherapy-induced cardiomyopathy has been established in multiple studies[5,40]. In another study, Kowallick et al[41] used this technique to measure left atrial mechanics in 10 healthy controls, 10 patients with HCM and 10 patients with heart failure with preserved LVEF (HFpEF).…”
Section: Reference Values Of Ft-cmr For Normal and Diseased Patientsmentioning
confidence: 99%
“…Of 10 non-Hodgkin's lymphoma patients with cardiac MRI before and 3 months after doxorubicin-based chemotherapy, 5 had a greater than 10% decreases in LV ejection fraction, and three had at least one new or progressive segment of gadolinium-delayed enhancement at follow-up [76]. Global circumferential strain was lower after chemotherapy, suggesting that MRI detected early functional changes [76]. Myocardial contrast enhancement increased by day 3 of anthracyclines, which predicted a decrease in LV ejection fraction at 28 days [77].…”
Section: Monitoring Chemotherapy-induced Cardiotoxicitymentioning
confidence: 99%